Marie : summer in the country, France, 1775 - Greene, Jacqueline Dembar (Girlhood journeys, 1997)
In August, 1775, while spending a month on her cousin's farm in the French countryside, Marie takes care of her younger sisters, picks vegetables, and helps her cousin find a way to earn money so she won't be sent away from home.